Fundamentals of digital image processing: a practical approach with examples in matlab. - Solomon, Chris; Breckon, Toby (WILEY, 2011)
"Given the timely topic and its user-friendly structure, this book can therefore target a suite of users, from students to experienced researchers willing to integrate the science of image processing to strengthen their research." (Ethology Ecology & Evolution, 1 May 2013).